Comparison of Psychological and Physiological Responses to Imposed vs. Self-selected High-Intensity Interval Training. Issue 11 (November 2019) - Kellogg, Erin; Cantacessi, Cheyann; McNamer, Olivia; Holmes, Heather; von Bargen, Robert; Ramirez, Richard; Gallagher, Daren; Vargas, Stacy; Santia, Ben; Rodriguez, Karen; Astorino, Todd A.
Abstract : Abstract: Kellogg, E, Cantacessi, C, McNamer, O, Holmes, H, von Bargen, R, Ramirez, R, Gallagher, D, Vargas, S, Santia, B, Rodriguez, K, and Astorino, TA. Comparison of psychological and physiological responses to imposed vs. self-selected high-intensity interval training. J Strength Cond Res 33(11): 2945–2952, 2019—High-intensity interval training elicits similar physiological adaptations as moderate intensity continuous training (MICT). Some studies report greater enjoyment to a bout of high-intensity interval exercise (HIIE) vs. MICT, which is surprising considering that HIIE is more intense and typically imposed on the participant. This study compared physiological and perceptual responses between imposed and self-selected HIIE. Fourteen adults (age = 24 ± 3 years) unfamiliar with HIIE initially performed ramp exercise to exhaustion to measure maximal oxygen uptake (VO2 max) followed by 2 subsequent sessions whose order was randomized. Imposed HIIE consisted of eight 60 seconds bouts at 80 percent peak power output (%PPO) separated by 60 seconds recovery at 10 %PPO. Self-selected HIIE (HIIESS ) followed the same structure, but participants freely selected intensity in increments of 10 %PPO to achieve a rating of perceived exertion (RPE) ≥7. During exercise, heart rate, VO2, blood lactate concentration (BLa), affect (+5 to −5), and RPE were assessed. Physical Activity Enjoyment Scale was measured after exercise. Results showed higher VO2 (+10%, p = 0.013), BLa ( p = 0.001), and RPE ( p = 0.001) in HIIESS vs. HIIEIMP, and lower affect ( p = 0.01), and enjoyment (87.6 ± 15.7 vs. 95.7 ± 11.7, p = 0.04). There was a significantly higher power output in self-selected vs. imposed HIIE (263.9 ± 81.4 W vs. 225.2 ± 59.6 W, p < 0.001). Data suggest that intensity mediates affective responses rather than the mode of HIIE performed by the participant.